Covid-19 dan Volatilitas Harga Saham Melalui Peran Mediasi Harga Emas - Sarwindah, Sarwindah; Hidayat, Widi; Murni, Siti Asiah (E-Jurnal Akuntansi; Vol 32 No 4 (2022), 2022)
This study aims to analyze the effect of Covid-19 which consists of the number of positive cases, the number of deaths, and the number of recoveries on stock price volatility through the mediating role of gold prices. The research population is a retail company listed on the Indonesia Stock Exchange with a research period from April 2020 to June 2021. The research sample was taken using purposive sampling, and analyzed using SEM PLS. The results of the analysis show that the number of positive cases has a significant negative effect on gold prices and the volatility of retail companies' stock prices. The number of deceased has a positive effect on the price of gold and the volatility of the stock price of retail companies. The number of recoveries has a positive effect on gold prices, but has no significant effect on stock price volatility. The mediating role explains that the price of gold has a mediating role on the effect of the number of positive cases and the number of deaths on stock price volatility, but does not have a mediating role on the effect of the number of recoveries on stock price volatility. Keywords: Covid-19; Gold Prices; Stock Price Volatility; Retail Companies .